If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(d + 6) = -2d + -12 Reorder the terms: 2(6 + d) = -2d + -12 (6 * 2 + d * 2) = -2d + -12 (12 + 2d) = -2d + -12 Reorder the terms: 12 + 2d = -12 + -2d Solving 12 + 2d = -12 + -2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '2d' to each side of the equation. 12 + 2d + 2d = -12 + -2d + 2d Combine like terms: 2d + 2d = 4d 12 + 4d = -12 + -2d + 2d Combine like terms: -2d + 2d = 0 12 + 4d = -12 + 0 12 + 4d = -12 Add '-12' to each side of the equation. 12 + -12 + 4d = -12 + -12 Combine like terms: 12 + -12 = 0 0 + 4d = -12 + -12 4d = -12 + -12 Combine like terms: -12 + -12 = -24 4d = -24 Divide each side by '4'. d = -6 Simplifying d = -6
| X+40+y=180 | | 2x+33=7x+3 | | 0.84xa=1 | | X^2-(1+3i)x-2+2i=0 | | 5+3(2a-5)-(a-6)= | | 5X+20y=345 | | 16x^2-96x+25y^2=256 | | 3x+20y=345 | | x+.07x=7.49 | | 4y-18=18 | | 15a-9a=72 | | n^3-m^3x^3/n-mx | | .025x=46 | | .025x=100 | | x=0.9x+3 | | 5(7-2x)=65 | | 2(x-3)=8+3x | | 11x+25=7x+1 | | 9x+7=4x-4 | | 5(y+3)=18-6y | | 5y-3x^3=127 | | 6x-1=15*-55 | | 4(4.5+2.5)-2y=5 | | 19x-6=6(x+3)-10 | | 2xy+4x-y=4 | | 4(9x+2)=153 | | P=-2b-3t-2t+b | | 46x-45x=1 | | 2w+30=60-x | | T=3a-4b+2a+b | | 3x-11=ax+6 | | x^2/3-11x/6-1=0 |